Strategic Management Technical Skills, Interpersonal Skills and Conceptual Skills of Officers in Manning KRI - Sutanto, Rudy (HM Publisher, 2021)
To achieve increased professionalism, the officers were disturbed by several shipwrecks that occurred. During the period 2013-2016, there have been 32 KRI accidents, the data can show an increasing trend of KRI accidents. In the maritime world, several ship accidents occur due to, among others, natural conditions, technical failures, shipping lane conditions, ship-related factors, human error, and cargo-related factors. This research uses a qualitative research approach with a case study method. From the research results, the ship which weighs 1,900 tons, has dimensions of 90.70 meters x 11.12 meters x 3.4 meters, is powered by 2 diesel engines, which can propel the ship up to a speed of 18 knots and can carry cargo up to 600 tons. happened when the ship finished docking. The habit factor of the ships above, anchoring like that, of course, has a reason, the Commander should in the learning process find out to enrich knowledge through experience to find the truth of the habit because one day it becomes one of the keys to work effectiveness and benefits in taking an action. If he learns from experience, leakage can be avoided. The results of the research show that expertise and responsibility are two of the pillars of professionalism, which are relevant to the case study of the shipwreck that the researcher lifted. The results of the ship accident case study, identified that to prevent accidents, officers must have technical, interpersonal, and conceptual skills. These three factors constitute a totality. This means that all three are interrelated and all KRI officers need some mix of all three. If one of them is not perfect or does not exist, it will have implications for shipping safety.